Lung function in elderly subjects with metabolic syndrome and type II diabetes: Data from the Berlin Aging Study II - Buchmann, Nikolaus; Norman, Kristina; Steinhagen-Thiessen, Elisabeth; Demuth, Ilja; Eckardt, Rahel (Zeitschrift für Gerontologie und Geriatrie, 2025)
Background Previous studies have indicated a relationship between type II diabetes (T2D), metabolic syndrome (MetS) and pulmonary function but the pathological mechanism responsible remains unclear. The aim of the current analysis within the Berlin Aging Study II (BASE-II) was to investigate the influence of abdominal obesity and muscle mass on pulmonary function in subjects with T2D and MetS. Material and methods A prebronchodilator pulmonary function test was carried out in 1369 subjects from the BASE-II (mean age 69 ± 4 years, 51.6 % women) where T2D was defined according to the German Diabetes Association (DDG) criteria, MetS according to the criteria of the International Diabetes Foundation (IDF), American Heart Association (AHA) and National Heart, Lung and Blood Institute (NHLBI) criteria from 2009 and pulmonary obstruction (obstructive lung disease, OLD) by the Global Initiative for Chronic Obstructive Lung Disease (GOLD) criteria of a forced expiratory volume in 1 s (FEV1 and forced vital capacity (FVC) ratio < 70 %. Results Of the subjects 50.9 % achieved a sufficient level of quality according to the GOLD guidelines and were analyzed with respect to the research question. The FEV1 and FVC were decreased in study participants with T2D and MetS and the lung volume decreased with an increasing number of MetS criteria. Parameters of body composition, such as waist circumference and muscle mass had a significant influence on lung volumes, independent of MetS or T2D. Discussion In this study MetS and T2D were associated with decreased lung volumes; however, muscle mass and abdominal obesity proved to be the most important factors influencing pulmonary function and could thus form the link between pulmonary function and MetS or T2D. Measurement of grip strength for the determination of muscle mass and waist circumference for determining abdominal obesity could contribute to the interpretation of the results of pulmonary function tests.